2018
DOI: 10.12659/msm.907138
|View full text |Cite
|
Sign up to set email alerts
|

Up-Regulation of Long Noncoding RNA SRA Promotes Cell Growth, Inhibits Cell Apoptosis, and Induces Secretion of Estradiol and Progesterone in Ovarian Granular Cells of Mice

Abstract: BackgroundIncreasing evidence indicates that long noncoding RNAs (LncRNAs) play a key role in multiple pathological processes. It has been shown that LncRNA steroid receptor RNA activator (SRA) is elevated in peripheral blood of patients with polycystic ovary syndrome (PCOS). The aim of this study was to assess the effect of elevated LncRNA SRA on ovarian granular cells of mice in vitro.Material/MethodsWe firstly isolated granular cells from mouse ovaries and over-expressed the LncRNA SRA by means of lentivira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 30 publications
0
41
0
Order By: Relevance
“…It was reported that SRA/SRAP depletion and SRAP overexpression lead respectively to a decrease and an increase in breast cancer cell motility (Yan et al, 2015). SRA was found to be increased in several other tumors, including hepatoma (Luo et al, 2017), ovarian cancers (Li et al, 2018), and cervical cancers (Eoh et al, 2017). Again, none of these studies utilized an in vivo metastasis model to address and validate the important role of SRA in cancer metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that SRA/SRAP depletion and SRAP overexpression lead respectively to a decrease and an increase in breast cancer cell motility (Yan et al, 2015). SRA was found to be increased in several other tumors, including hepatoma (Luo et al, 2017), ovarian cancers (Li et al, 2018), and cervical cancers (Eoh et al, 2017). Again, none of these studies utilized an in vivo metastasis model to address and validate the important role of SRA in cancer metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs) are important components of non-coding RNAs [24]. lncRNAs can regulate the expression of target genes in a variety of ways, such as cis, trans, or combined with miRNAs, so it is not easy to determine their target genes [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…The roles of lncRNAs in organ development, cancer treatment, and aging have been widely reported over the past decades [27][28][29]. In addition, Hu et al found that lncRNAs play an important role in the differentiation of T helper subsets [30]; Li et al found that the levels of 17β-estradiol (E2) and progesterone in mice ovarian cells increased after overexpression of lncRNA SRA [24]. A recent study found that androgen and estrogen influence lncRNA expression during penis development in marsupials [31].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, SRA was also found to contribute to several pathological processes, including obesity, tumorigenesis, and cardiomyopathy [15]. Specifically in the process of tumorigenesis, SRA was reported to be actively involved in the progression of benign tumors and malignant cancers that are related to steroid or sex hormones, including ovarian endometriosis [16], polycystic ovary [17], uterine myoma [18], as well as endocrine cancers, breast cancers, ovarian cancers [19], and cervical cancers [20]. Because some pigmentary diseases have gender differences, for example, melasma preferentially affects woman, we remain interested whether SRA, which helps regulate cellular pathways related to steroid or sex hormone, regulates melanogenesis in melanocytes.…”
Section: Introductionmentioning
confidence: 99%